Graves Disease and Inflammatory Bowel Disease: A Bidirectional Mendelian Randomization - Xian, Wei; Wu, Dide; Liu, Boyuan; Hong, Shubin; Huo, Zijun; Xiao, Haipeng; Li, Yanbing (The journal of clinical endocrinology and metabolism, 2023)
Abstract Context Both Graves disease (GD) and inflammatory bowel disease (IBD) are common autoimmune diseases that severely damage a patient’s quality of life. Previous epidemiological studies have suggested associations between GD and IBD. However, whether a causal relationship exists between these 2 diseases remains unknown. Objective To infer a causal relationship between GD and IBD using bidirectional 2-sample Mendelian randomization (MR). Methods We performed bidirectional 2-sample MR to infer a causal relationship between GD and IBD using genome-wide association study summary data obtained from Biobank Japan and the International Inflammatory Bowel Disease Genetic Consortium. Several methods (random-effect inverse variance weighted, weighted median, MR-Egger regression, and MR-PRESSO) were used to ensure the robustness of the causal effect. Heterogeneity was measured based on Cochran's Q value. Horizontal pleiotropy was evaluated by MR-Egger regression and leave-one-out analysis. Results Genetically predicted IBD may increase the risk of GD by 24% (odds ratio [OR] 1.24, 95% CI 1.01-1.52, P = .041). Crohn disease (CD) may increase the risk of GD, whereas ulcerative colitis (UC) may prevent patients from developing GD. Conversely, genetically predicted GD may slightly increase the risk of CD, although evidence indicating that the presence of GD increased the risk of UC or IBD was lacking. Outlier-corrected results were consistent with raw causal estimates. Conclusion Our study revealed a potentially higher comorbidity rate for GD and CD. However, UC might represent a protective factor for GD. The underlying mechanism and potential common pathways await discovery.